Retrospective evaluation of doxorubicin–piroxicam combination for the treatment of transitional cell carcinoma in dogs. (3rd January 2013) - Robat, C.; Burton, J.; Thamm, D.; Vail, D.
<x xml:space="preserve">Abstract</x> Objectives To determine whether doxorubicin–piroxicam combination is safe and has activity against transitional cell carcinoma in dogs. Methods Data was collected retrospectively from 34 dogs from two institutions over a 6‐year period. Signalment, clinical presentation, treatment specifics, adverse events, response, progression‐free survival and overall survival time were evaluated. Results Dogs received doxorubicin every 3 weeks and daily piroxicam; 17 dogs (50%) had surgery. Clinical presentations were those typically reported for transitional cell carcinoma. Mean number of doses administered was 3·5. Of the 23 dogs with measurable disease, 14 (60·5%) had stable disease, 7 (30·5%) had progressive disease and 2 (9%) a partial response. Adverse events were generally manageable, and gastrointestinal in origin; one dog died of treatment‐related complications. Overall median progression‐free survival and overall survival were 103 and 168 days, respectively. Cytoreductive surgery did not result in prolongation of progression‐free survival, but significantly prolonged overall survival. All dogs but one died as a result of disease progression. Clinical Significance Doxorubicin–piroxicam combination therapy is well‐tolerated in dogs with transitional cell carcinoma although progression‐free survival, overall survival and biological response rates appear modest. Combination with surgery appears to offer a survival advantage; however, this may reflect tumour location and volume. Prospective studies are necessary to compare activity of combination doxorubicin–piroxicam to currently applied therapies.